The Political Mobility of China's Central State-Owned Enterprise Leaders. (8th January 2018) - Leutert, Wendy
Abstract: Extensive research on the political mobility of Chinese officials at central, provincial, municipal and county levels has yet to fully consider an important group of elites – the leaders of China's core central state-owned enterprises (SOEs). This paper presents the first systematic analysis of their political mobility between 2003 and 2012 using an original biographical dataset with 864 leader-year observations. Under the Hu Jintao administration, these leaders emerged as a distinctive group within China's top political elite: increasingly well-educated but lacking experience beyond state-owned industry, with both lengthening leadership tenures and years of previous work in their companies. Instead of a "revolving door" through which these individuals rotate routinely between state-owned business and the Party-state to positions of successively higher rank, a top executive posting was most often a "one-way exit" to retirement. Of those who advanced politically, virtually all were transferred laterally along three career pathways with little overlap: to other core central SOEs; provinces; and the centre. This paper underscores the theoretical importance of disaggregating types of lateral transfer to research on Chinese officials' political mobility and the cadre management system. 摘要: 目前关于中国中央、省部级、地市级和县级的官员政治流动的广泛研究尚未充分考虑到中国中央国有企业 (央企) 领导人这一重要政治精英群体。本文运用原创性的、涵盖 864 笔央企领导人和年份的简历数据库, 首次系统性地研究了 2003 年到 2012 年的央企领导人政治流动。研究发现, 在胡锦涛政府期间, 他们成长为中国高层政治精英的独特群体, 主要表现为他们的教育水平在不断提高, 但缺乏国企之外的工作经历, 同时他们的领导任期偏长, 而且长期在同一企业工作。央企高管职位往往是通往退休的单行道, 而非成为国企和政府体制之间例行的晋升旋转门。而那些政治上得到晋升的央企高管, 则几乎都通往其他央企、省级部门和中央部门这三个绝少交叉的职业轨道。本文强调在研究中国官员的政治流动和干部管理制度时, 分解不同类型的横向流动的理论意义。